Characterization of a cohort of metastatic lung cancer patients harboring KRAS mutations treated with immunotherapy: differences according to KRAS G12C vs. non-G12C - Notario, Lucía; Cucurull, Marc; Cerdà, Gabriela; Sanz, Carolina; Carcereny, Enric; Muñoz-Mármol, Ana; Hernández, Ainhoa; Domènech, Marta; Morán, Teresa; Sánchez-Céspedes, Montse; Costa, Marta; Mate, Jose-Luis; et al. (Frontiers in Oncology, 2023)
Approximately 20% of lung adenocarcinomas harbor activating mutations at KRAS, an oncogene with the ability to alter the tumor immune microenvironment. In this retrospective study, we examined 103 patients with KRAS-mutant lung adenocarcinoma who were treated with immunotherapy-based regimens and we evaluated the clinical outcomes according to PD-L1 expression and the type of KRAS mutation. Among all patients included, 47% carried KRAS G12C mutation, while 53% harbored KRAS non-G12C mutations. PD-L1 status was available for 77% of cases, with higher expression among KRAS G12C tumors (p=0.01). Better overall survival and progression-free survival was observed in high PD-L1 expression tumors, regardless of KRAS mutation type. The heterogeneous nature of KRAS-mutant tumors and the presence of other co-mutations may contribute to different outcomes to immunotherapy-based strategies.